Genome-Wide Association Study to Map Genomic Regions Related to the Initiation Time of Four Growth Stage Traits in Soybean - Yan, Wenliang; Karikari, Benjamin; Chang, Fangguo; Zhao, Fangzhou; Zhang, Yinghu; Li, Dongmei; Zhao, Tuanjie; Jiang, Haiyan (Frontiers in Genetics, 2021)
Time to flowering (DF), pod beginning (DPB), seed formation (DSF) and maturity initiation (DMI) in soybean (Glycine max [L.] Merr) are important characters of growth stage traits (GSTs) in Chinese summer-sowing soybean and influenced by genetic as well as environmental factors. To better understand the molecular mechanism underlying initiation time of GSTs, we investigated four GSTs of 309 diverse soybean accessions in six different environments and Best Linear Unbiased Prediction values. Furthermore, genome-wide association study was conducted by a Fixed and random model Circulating Probability Unification method using over 60,000 single nucleotide polymorphism (SNP) markers to identify the significant quantitative trait nucleotide (QTN) regions with phenotypic data. As a result, 212 SNPs within 102 QTN regions were associated with four GSTs. Of which, 8 stable regions were repeatedly detected in least three datasets for one GST. Interestingly, half of the QTN regions overlapped with the previously reported quantitative trait loci or well-known soybean growth period genes. The hotspots associated with all GST were concentrated on chromosome 10 from which the E2 (Glyma10g36600) gene with a known function in regulating flowering and maturity in soybean. This genomic region may account for the strong correlation among the four GSTs. All the significant SNPs in the remaining 7 QTN regions could cause the significant phenotypic variation with both the major and minor alleles. Two hundred and seventy-five genes in soybean and their homologs in Arabidopsis were screened within ±500 kb of 7 peak SNPs in the corresponding QTN regions. Most of the genes are involved in flowering, response to auxin stimulus, regulation of seed germination, among others. The findings reported here provide insight for genetic improvement which will aid in breeding of soybean cultivars that will be adapted to the various summer sowing areas in China and beyond.